Analysis of different stator winding topologies for fractional horse power brushless direct current motors. Issue 12 (3rd September 2021) - Krall, Felix; Muetze, Annette
Abstract: The number of auxiliary electric drives can exceed 100 for luxury cars. Due to their ever‐increasing prevalence, the electromagnetic emissions (EME) of these drives are becoming increasingly important. This work explores the influence of four different stator winding topologies on the electromagnetic emissions and the efficiency performance of fractional horsepower (FHP) brushless direct current (BLDC) drives. Two monofilar windings with a wire diameter of 0.15 and 0.27 mm, an untwisted bifilar winding, and a twisted bifilar winding are inspected. The parasitic stator to winding coupling capacitance is the motor's main source for common mode currents and thus, for radiated emissions. A three‐media capacitance model is introduced to allow estimating this coupling path in the design phase of the motor. Twisting the phases of a bifilar winding reduces the excitation of this path. Therefore, the radiated emissions are reduced by 5 d B μ V/m ${B}_{μ \text{V/m}}$ . The stator winding topology also affects the winding resistance and thus the efficiency. The monofilar winding with a wire diameter of 0.27 mm shows the lowest level of consumed power, followed by the monofilar winding with a wire diameter of 0.15 mm, the untwisted bifilar winding and the twisted bifilar winding.